Learning about Grandparents’ Past Life: Reflections of Grandchildren in an Intergenerational Reminiscence Project for Asian American Families - Ling Xu; Aaron Hagedorn; Minjaal Raval (Behavioral Sciences, 2023)
Immigration, aging, and dementia often result in a triple jeopardy for Asian American older adults. To improve the well-being of Asian American older adults as well as generational bonding, an Intergenerational Grandparent–Grandchild Reminiscence Program was developed. This paper qualitatively reports on the weekly reflections from the grandchild participants of this program. Older grandparents received six sessions of life-review discussion with their grandchildren remotely or in person for approximately 1 h each week for 6 weeks. Each grandchild (n = 12) provided a written reflection each week after talking with their grandparent. The qualitative data were organized and analyzed using the five phases of the rigorous and accelerated data reduction (RADaR) technique. The results show three categories of themes, as follows: Category 1—Positive experience: more connection with the grandparent; learning more about the grandparent’s past life experience; and more engagement; Category 2—Challenging experience: over-explaining things; language or vocabulary barriers; and overly-broad topics; Category 3—Strategy to lead the discussion: using guiding questions in the manual; using translators; spending time together; and taking notes. The results show that the intergenerational reminiscence program is promising for bonding and connection in the grandparent–grandchild relationship. Participants also gained knowledge and experienced challenges when talking with their grandparents during the program.